Shining a light on fish at night: An overview of fish and fisheries in the dark of night, and in deep and polar seas - Hammerschlag, N.; Meyer, C.; Grace, M.; Kessel, S.; Sutton, T.; Harvey, Euan; Paris-Limouzy, C.; Kerstetter, D.; Cooke, S. (Rosenstied School of Marine and Atmospheric Science of the University of Miami, 2017)
In aquatic environments, what one observes during the day can differ substantially by night. Te species composition and associated ecological processes that occur during the day are often different than night. In polar seas and at great depths, "night" can span, months, years, and beyond. Teleosts and elasmobranchs have evolved unique sensory and behavioral modalities for living in darkness. As a consequence, fshers have adopted unique strategies for exploiting fsh at night or in dark systems. We propose that neglecting the night has led to an incomplete understanding of aquatic organismal ecology, population/community dynamics, and ecosystem function with consequences for fsheries conservation management. To address this knowledge gap and stimulate the exchange of new data and ideas on behaviors, patterns, and processes relating to fsh and fsheries in darkness, Fish at Night: an international symposium was held in Miami, Florida (USA), from 18 to 20 November, 2015. Here, we synthesize the fndings from the symposium, providing an overview on the state-ofknowledge of fsh studies in the dark, identifying critical information gaps, and charting a course for future research. We focus our commentary and synthesis on six areas: (1) nocturnal fsh behavior and ecology; (2) fshing, fsheries, and enforcement; (3) deep and polar seas; (4) diel fsh distribution and abundance comparisons; (5) methods for studying fsh in darkness; (6) human threats to fsh at night; and (7) larval fsh at night. Taken together, we attempt to "shine a light" on fsh at night, generating a greater interest and understanding of fshes and fsheries during darkness.